Comparative Analysis on Vestibular Schwannoma Surgery with and without Intraoperative Fluorescein Sodium Enhancement - Amer A. Alomari; Sadeen Sameer Eid; Flavia Fraschetti; Silvia Michelini; Luciano Mastronardi (Brain Sciences, 2024)
Background: Vestibular schwannoma (VS), also known as acoustic neuroma, is a benign, well-encapsulated, and slow-growing tumor that originates from Schwann cells, which form the myelin sheath around the vestibulocochlear nerve (VIII cranial nerve). The surgical treatment of this condition presents a challenging task for surgeons, as the tumor’s location and size make it difficult to remove without causing damage to the surrounding structures. In recent years, fluorescein sodium (FS) has been proposed as a tool to enhance surgical outcomes in VS surgery. This essay will provide an analytical comparison of the use of FS in VS surgery, evaluating its benefits and limitations and comparing surgical outcomes with and without FS-assisted surgery. Methods: In a retrospective study conducted at San Filippo Neri Hospital, we examined VS cases that were operated on between January 2017 and December 2023. The patients were divided into two groups: group A, which consisted of patients who underwent surgery without the use of FS until January 2020 (102 cases), and group B, which included patients who underwent surgery with FS after January 2020 (55 cases). All operations were performed using the retrosigmoid approach, and tumor size was classified according to the Koos, et al. classification system. The extent of surgical removal was evaluated using both the intraoperative surgeon’s opinion and postoperative MRI imaging. Preoperatively and postoperatively, facial nerve function and hearing were assessed. In group B, FS was used to assist the surgical procedures, which were performed using a surgical microscope equipped with an integrated fluorescein filter. Postoperative clinical and MRI controls were performed at six months and annually, with no patients lost to follow-up. Results: This study investigated the impact of intraoperative fluorescein exposure on tumor resection and clinical outcomes in patients with VS. The study found a statistically significant difference in the tumor resection rates between patients who received fluorescein intraoperatively (p = 0.037). Further analyses using the Koos classification system revealed a significant effect of fluorescein exposure, particularly in the Koos 3 subgroup (p = 0.001). Notably, no significant differences were observed in hearing loss or facial nerve function between the two groups. A Spearman correlation analysis revealed a positive correlation between tumor size and Koos, age, and size, but no significant correlation was found between facial nerve function tests. Conclusions: FS-assisted surgery for VS may potentially enhance tumor resection, allowing for more comprehensive tumor removal.